Adaptive immune responses in patients requiring revision after total knee arthroplasty. Issue 5 (2nd October 2022) - Jenkins, Daniel; Phalke, Swati; Bell, Richard; Lessard, Samantha; Gupta, Sanjay; Youssef, Mark; Tam, Kathleen; Nocon, Allina; Rivera‐Correa, Juan; Wright, Timothy; Sculco, Thomas; Otero, Miguel; et al.
Abstract: Dissatisfaction occurs in nearly 20% of patients after total knee arthroplasty (TKA); however, there remains only limited understanding of the biologic mechanisms that may contribute to suboptimal postoperative outcomes requiring revision surgery. Expansion of effector T and B cells, could promote an abnormal healing response via local or peripheral immune system mechanisms and contribute to inferior outcomes necessitating revision TKA. In this pilot study, we hypothesized that patients suffering from complications of arthrofibrosis or instability may exhibit differences in adaptive immune function. Patients ( n = 31) undergoing revision TKA for an indication of arthrofibrosis or instability were prospectively enrolled. Whole blood and synovial fluid (SF) from the operative knee were collected at time of surgery. Peripheral blood mononuclear cells were isolated and analyzed by flow cytometry. Serum and SF were assessed for immunoglobulin levels by Luminex and antiphospholipid antibodies by enzyme‐linked immunoassay. No significant differences were observed in peripheral blood T/B cell populations or serum immunoglobulins levels between groups. SF analysis demonstrated significant differences between the two groups, with higher levels of immunoglobulin G1 (IgG1) ( p = 0.0184), IgG3 ( p = 0.0084) and antiphosphatidyl serine IgG ( p = 0.034) in arthrofibrosis relative to instability patients. Increased levels of both IgG subclasses and antiphospholipid antibodies in the SF suggest that intra‐articular T‐B cell interactions, potentially triggered by exposure to apoptotic components generated during post‐op healing, could be functioning as a source of immune complexes that fuel fibrous tissue growth in arthrofibrotic patients.